DEVELOPMENT THROUGH THE EYES OF THE DEAF IN HIGHER EDUCATION: THE CASE OF SPECIAL EDUCATION STUDENTS IN QUEZON, PHILIPPINES (Proceedings of International Conference on Special Education, 2015)
There are around 360 million people with hearing loss worldwide according to 2014 report of the World Health Organization (WHO), but only few researchers have studied this particular population of people with special needs. This study fills important gaps in the literature about non-Western deaf communities. Amid endeavors on their development through special education, there had been few efforts that aimed to surface their own perspectives (and consequently, hear their “voices”) on development. This study identified how college deaf students of Bartimaeus Center for Alternative Learning in Quezon, Philippines view development using visual communication techniques. Complete enumeration was employed. The Constructivist Theory of Perception guided the study, which states that past experiences and stored information influence perception. Thematic analysis generated these development themes: social development; pleasant environment; interpersonal relationships; availability of resources; employment; infrastructure development; values; and peace and security. Using the National Economic and Development Authority (NEDA) development indicators on inclusive growth, findings showed the deaf students’ views on development were similar from the development indicators of the government. The only exception was the perception of development as having good interpersonal relationships, which is important for deaf people in their development, but not included in the NEDA’s indicators. This points to the need  of eliciting their perspectives on matters affecting them as they have the capacity to say something of utmost significance. Visual communication techniques can be used as sites for such meaningful responses and to listen to their valuable ideas.